Effectiveness of Rehabilitation Activities for Addicts and Victims of Drug Abuse in Sleman District, Yogyakarta - Arif Nur Hidayat; Tegar Puji Ichtiary; Ida Kartini Albirru (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The high rate of drug abuse in Yogyakarta, especially in Sleman Regency which is the most vulnerable location, is the background of this study. The purpose of this study was to determine the effectiveness of rehabilitation activities for victims of drug abuse, psychotropics, and addictive substances in Sleman Regency, with a focus on the Sembada Bersinar Clinic. This study used a qualitative descriptive method, with data collection techniques through observation and documentation. The results of the study showed that rehabilitation activities at the Sembada Bersinar Clinic had mostly been running effectively. Effectiveness was seen in the delivery of program information, restoration of victim awareness through spiritual guidance, continuity of the post-rehabilitation recovery process, socialization through social media, and integration and communication with stakeholders. The process of accepting participants and recruiting experts was also in accordance with standards. It was concluded that the rehabilitation program had been running effectively, but one aspect was found that was not optimal, namely the process of continuous coaching and training for administrators or rehabilitation experts.